BS EN 12102-1. Air conditioners, liquid chilling packages, heat pumps, process chillers and dehumidifiers with electrically driven compressors. Determination of the sound power level. Part 1. Air conditioners, liquid chilling packages, heat pumps for space heating and cooling, dehumidifiers and process chillers (20th May 2021) - British Standards Institution,
No abstract available